2016
DOI: 10.1007/s11356-016-6530-7
|View full text |Cite
|
Sign up to set email alerts
|

Chloride ion-driven transformation from Ag3PO4 to AgCl on the hydroxyapatite support and its dual antibacterial effect against Escherichia coli under visible light irradiation

Abstract: Visible light-driven photocatalytic inactivation of Escherichia coli was performed using hydroxyapatite-supported Ag3PO4 nanocomposites (Ag3PO4/HA). The antibacterial performance was evaluated by the methods of zone of inhibition plates and minimum inhibitory concentration test. X-ray diffraction (XRD) and transmission electron microscopy (TEM) were employed to investigate the instability and transformation of the nanocomposite by comparing the crystalline, phase, and the morphology before and after exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…However, the presence of NaCl and NaH 2 PO 4 at concentrations higher than 1 mmol L −1 could affect the analytical results due to the formation of AgCl or Ag 3 PO 4 precipitate. 35 Consequently, less Ag + ions from the Ag-HAP were available for chemical reduction and the AgCl formed led to a material color change from off-white to pale gray.…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of NaCl and NaH 2 PO 4 at concentrations higher than 1 mmol L −1 could affect the analytical results due to the formation of AgCl or Ag 3 PO 4 precipitate. 35 Consequently, less Ag + ions from the Ag-HAP were available for chemical reduction and the AgCl formed led to a material color change from off-white to pale gray.…”
Section: Resultsmentioning
confidence: 99%
“…Recently much effort has been devoted to study of Ag3PO4, which is a highly promising photocatalytic material with an indirect band gap of ~2.36 eV and high quantum efficiency (up to 90 % at 420 nm) (Hewer et al, 2014;Kumar ete al., 2014). Enhanced photoinduced catalytic (Hewer et al, 2014;Kumar et al, 2014) and antibacterial (Hong et al, 2016;Piccirillo et al, 2015) activity of Ag3PO4 compared to TiO2 is reported. In particular, the antimicrobial activity of Ag3PO4 is widely studied, mainly because Ag and some of its compounds are used as an efficient disinfectants for thousands of years (Silvestry-Rodriguez et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, photoinduced antibacterial activity of Ag3PO4 is frequently evaluated by a certain bacterial concentration adjusted by serial dilution of sterilized NaCl solution (Roy et al, 2012), liquid nutrient medium (Sadowski et al, 2015), phosphate buffered saline (PBS) solution (Liu et al, 2012), or in Luria-Bertani culture medium (Roy et al, 2012). As reported by Hong et al (Hong et al, 2016), a transformation of Ag3PO4 to AgCl in the presence of Clions in Ag3PO4/hydroxyapatite composite occurs. As AgCl itself possess photoinduced catalytic (Dong et al, 2012;Hu et al, 2006;Rehan et al, 2018) and antibacterial (Chen et al, 2015;Kang et al, 2016) activity, Hong et al refers to it as a dual antibacterial effect.…”
Section: Introductionmentioning
confidence: 99%
“…Works involving Ag3PO4 silver orthophosphate have been expressive mainly due to their excellent properties optical, semiconductor [55][56][57][58][59][60][61][62], photocatalytic and antimicrobial [63][64][65][66] The particle size [57,[67][68][69][70], synthesis methods [61,[71][72][73], effect of the localized surface plasmon resonance (LSPR) induced by metallic nanoparticles [68,74,75], as well as the morphology [56,76,77] directly interfere in photocatalytic and biologic Ag3PO4 properties [78][79][80]. Moreover, Ag3PO4 presents high instability when irradiated, which impairs its use in photocatalys with conventional light sources [62,81].…”
Section: Introductionmentioning
confidence: 99%